A new species of Crenicichla (Perciformes: Cichlidae) from the Ventuari River, Upper Orinoco River Basin, Amazonas State, Venezuela - Montaña, Carmen G.; López-Fernández, Hernán; Taphorn, Donald C. (Zootaxa, 2008)
We describe a new species of the genus Crenicichla Heckel, 1840, from the Ventuari River, a tributary of the Orinoco River in southern Venezuela. Crenicichla zebrina is distinguished from all other species in the genus by its unique coloration pattern, including the combination of a large, dark, vertically oriented, more or less oval-shaped humeral spot, and thin, dark bars, separated by narrow, vertical, yellowish bars extending between the dorsal and anal fin base on the caudal half of the body. Crenicichla zebrina is included in the putative C. acutirostris group (9 species) and represents the only species in the group known to date from the Orinoco basin.